A Taxonomy for Heavy-Duty Telemanipulation Tasks Using Elemental Actions. (29th October 2013) - Owen-Hill, Alexander; Breñosa, José; Ferre, Manuel; Artigas, Jordi; Aracil, Rafael
In the maintenance of large scientific facilities, telemanipulation procedures can involve various subprocedures which in turn are made up of a sequence of subtasks. This work presents a taxonomy which describes a set of elemental actions for heavy-duty telemanipulation, along with an example of these actions in a standard maintenance subprocedure. As maintenance tasks are often very different at high-level, this generalized way of deconstructing tasks allows a highly adaptable approach to describe the sequence of any procedure, which can then be used for such applications as task monitoring, automation or detection of incomplete tasks. We describe in detail the properties of each elemental action and apply the taxonomy to an example subprocedure to show how the process can be generalizable. An automatic state-machine creation stage is shown, which would be used at the task scheduling stage to simplify calculations carried out during the moment-by-moment execution of the task.